High temperature polymer electrolyte membrane fuel cells with Polybenzimidazole-Ce0.9Gd0.1P2O7 and polybenzimidazole-Ce0.9Gd0.1P2O7-graphite oxide composite electrolytes - Singh, Bhupendra; Devi, Nitika; Srivastava, Avanish Kumar; Singh, Rajesh K.; Song, Sun-Ju; Krishnan, N. Nambi; Konovalova, Anastasiia; Henkensmeier, Dirk (Elsevier BV, 2018)
In this work, polybenzimidazole based composite membranes are fabricated using polybenzimidazole, Ce0.9Gd0.1P2O7 and graphite oxide by solution casting procedure. The microstructural, mechanical and electrical properties of the phosphoric acid-doped composite membranes are characterized for fuel cell applications. Addition of graphite oxide in the composite leads to improvement in homogeneous dispersion of higher amount, 31 wt%, of Ce0.9Gd0.1P2O7. With the increasing amount of Ce0.9Gd0.1P2O7 in the composite membranes the amount of phosphoric acid loading decreases, but the proton conductivity of the composite membrane is higher than that is reported for the phosphoric acid-doped polybenzimidazole membranes. At 180 degrees C, a maximum conductivity of 182 mS cm(-1) for polybenzimidazole/Ce0.9Gd0.1P2O7 membrane with 24 wt% Ce0.9Gd0.1P2O7 and 199 mS cm(-1) for polybenzimidazole/Ce0.9Gd0.1P2O7/graphite oxide membrane with 31 wt% Ce0.9Gd0.1P2O7 is observed. The H-2-Air fuel cells operating at 160 degrees C with similar to 250 mu m thick polybenzimidazole/Ce0.9Gd0.1P2O7 electrolyte shows open circuit voltage of 0.938 V and maximum power density of 255 mW cm(-2) with 640 mA cm(-2) current at 160 degrees C whereas the corresponding values with similar to 200 mu m thick polybenzimidazole/Ce0.9Gd0.5P2O7/graphite oxide membrane are 0.976 V and 307 mW cm(-2) with 800 mA cm(-2) current, respectively. However, irrespective of the increased conductivity at the higher temperatures, the maximum power density decreases with increasing temperature > 160 degrees C.